Highland heat ebook - Wine, Mary (Hot Highlanders, 2011)
Praise for To Conquer a Highlander: "Not to be missed." —Lora Leigh, New York Times bestselling author of Lion's Heat Ruined, Betrayed, and banished... As brave as she is impulsive, Deirdre Chattan's tendency to follow her heart and not her head has finally tarnished her reputation beyond repair. But when powerful Highland Laird Quinton Cameron finds her, he doesn't care about her past—it's her future he's about to change... But it's never too late for redemption... From the moment Quinton sets eyes on Deirdre Chattan, rational thought vanishes. For in her eyes he sees a fiery spirit that matches his own, and he'll be damned if he'll let such a wild Scottish rose wither under the weight of a nun's habit... With nothing to lose, Deirdre and Quinton band together to protect king and country. But what they can accomplish alone is nothing compared to what they can build with their passion for each other... What readers say about Mary Wine's Scottish romance: "Simply extraordinary." "Scottish Highlands, rugged and virile warriors—there is nothing like it." "Plenty of romance, action, intrigue, and danger."